(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The study aimed at investigating the relationship between supplier development and supply chain performance of fertilizer manufacturing companies in Nigeria. To achieve the study’s objectives, two specific goals were established, and corresponding null hypotheses were formulated to address the research questions aligned with these objectives. A correlational research design was employed to ensure the effective collection and analysis of necessary data. Primary data collection methods were utilized, and a census approach was adopted to include the entire target population in the study. The sample comprised five managers from each of the seven fertilizer manufacturing companies operating in Nigeria, totaling 35 respondents. To ensure the reliability of the research instrument, Cronbach’s Alpha was employed, with a reliability threshold set at 0.70. The study used the Pearson Product-Moment Correlation to measure the relationship between supplier development and the various metrics of supply chain performance, specifically innovativeness and responsiveness. The Statistical Package for Social Sciences (SPSS) software, version 23.0 was used in conducting the analysis. Findings of the study revealed a positive and significant relationship between supplier development and the supply chain performance of fertilizer manufacturing firms in Nigeria. Consequently, the study concludes that supplier development has a significant impact on the supply chain performance of these companies. Based on these findings, it is recommended that the management of fertilizer manufacturing companies in Nigeria should provide targeted education and training to partner suppliers, equipping them with essential knowledge about the firm’s business focus and expectations.